A prospective study of hidden cases of beta thalassemia trait in voluntary blood donors at tertiary care hospital of south Gujarat - Dr. Hemali J. Tailor; Dr. Prashant R. Patel (Tropical Journal of Pathology and Microbiology, 2019)
Background: Hemoglobinopathies represent a significant national health burden in India. The two most common causes of microcytic (MCV less than 80 fl) anemia are iron deficiency anemia and beta-thalassemia trait. In most of these cases a trial of iron treatment done but in populations where Thalassemia is common, like in India, this approach leads to unnecessary iron therapy / iron overload. Therefore the study has been done to detect hidden cases of beta thalassemia in voluntary blood donors with microcytosis.Materials and Methods: Total 393 donor samples were analyzed for complete blood count, ESR and serum ferritin levels. Mentzer index was calculated by MCV/RBC count formula. HPLC test was done on 12samples with Mentzer index <13 for quantification of HbA2.Results: Out of 393 blood donors, 384 were males and 9 were females. Low MCV detected in 58 samples [14.75%]. Out of 12 samples tested by HPLC, 6 cases were Beta thalassemia trait [1.53%], 5 were normal and one was? sickle cell trait/ ? Hb D trait. Out of 6 BTT cases, 3 cases show normal ferritin value, 2 with low ferritin level and one with high ferritin level.Conclusions: The study revealed a high prevalence of IDA and BTT in blood donors and a higher probability of finding these in the microcytic samples. Screening for thalassemia trait by routine blood counts in all the blood donor samples and if required by HPLC, should be included in the standard blood testing policy after blood donation.